"Bantay malnutrisyon 24-oras" Barangay Mayang, Tubungan, Iloilo - Cueva, Lorelie
This study aims to improve the nutritional status of at least 80% of the malnourished, 0-6 year-old children in Barangay Mayang, Tubungan, Iloilo by end of March 2006.